The Neural Correlates of Visual and Auditory Cross-Modal Selective Attention in Aging - Rienäcker, Franziska; Van Gerven, Pascal W. M.; Jacobs, Heidi I. L.; Eck, Judith; Van Heugten, Caroline M.; Guerreiro, Maria J. S. (Frontiers in Aging Neuroscience, 2020)
Age-related deficits in selective attention have been demonstrated to depend on the sensory modality through which targets and distractors are presented. Some of these investigations suggest a specific impairment of cross-modal auditory selective attention. For the first time, this study is taking on a whole brain approach while including a passive perception baseline, to investigate the neural underpinnings of selective attention across age groups, and taking the sensory modality of relevant and irrelevant (i.e., distracting) stimuli into account. Sixteen younger (mean age = 23.3 years) and 14 older (mean age = 65.3 years), healthy participants performed a series of delayed match-to-sample tasks, in which participants had to selectively attend to visual stimuli, selectively attend to auditory stimuli, or passively view and hear both types of stimuli, while undergoing 3T fMRI. The imaging analyses showed that areas recruited by cross-modal visual and auditory selective attention in both age groups included parts of the dorsal attention and frontoparietal control networks (i.e., intraparietal sulcus, insula, fusiform gyrus, anterior cingulate, and inferior frontal cortex). Most importantly, activation throughout the brain did not differ across age groups, suggesting intact brain function during cross-modal selective attention in older adults. Moreover, stronger brain activation during cross-modal visual versus cross-modal auditory selective attention was found in both age groups, which is consistent with earlier accounts of visual dominance. In conclusion, these results do not support the hypothesized age-related deficit of cross-modal auditory selective attention. Instead, they suggest that the underlying neural correlates of cross-modal selective attention are similar in younger and older adults.